DEFENSE DIPLOMACY IN RESOLVING THE PROBLEM OF INDONESIA’S TERRITORIAL BOUNDARIES WITH MALAYSIA IN TANJUNG DATU - Sukirno, Apriles Lusein; Prabawa, Eka; Mukti, Sopan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Based on the fact that as an archipelago, Indonesia shares borders with neighboring countries in Southeast Asia. With a large number of territorial borders of Indonesia and other countries, it has resulted in various cooperative relationships or various border problems between Indonesia and these neighboring countries. The purpose of this study was to determine the form of defense diplomacy and its analysis to include the Tanjung Datu Phase as the Indonesia-Malaysia Outstanding Boundary Problem (OBP). The writing method used is qualitative, wherein in this analysis, the writer does not make calculations. The findings of this study are the subject of Indonesia's defense diplomacy to include the Tanjung Datu Phase as OBP Indonesia-Malaysia, namely the national regional coordination committee (Pankorwilnas), Directorate of Topography of the Army, Ministry of Defense, Ministry of Home Affairs, and Outstanding Boundary ProblemÂ (OBP). Meanwhile, the object of Indonesia's defense diplomacy to include the Tanjung Datu Phase as OBP Indonesia-Malaysia is in the form of Indonesia's goal, namely as the implementation of national interests in achieving its territorial sovereignty, and this is included in the scope of the defense.